Analysis of Governance and Efficiency on Zakat Distribution: Evidence From Indonesia - Novendi Arkham Mubtadi; Dewi Susilowati (International Journal of Zakat, 2018)
This study analysesand identifies the governance factor(s) that influence zakat disbursement efficiency for Indonesia’s National Zakat Board (BAZNAS)in four district of Central Java Province, namely Banyumas, Purbalingga, Banjarnegara, and Kebumen. This research examines how the zakat institution in Indonesia has improved in terms of disbursement activities over the past 5 years (2011-2015).This is a quantitative research study that uses two approaches of efficiency analysis, namely (i) zakat disbursement efficiency measurement (ratio analysis) and (ii) identification of governance factor(s) that influence the zakat disbursement efficiency of the zakat institutions (regression analysis). Eviews 9 was used in data calculation. In the first approach, there are three efficiency measures: disbursement efficiency, cost efficiency and time efficiency. In the second approach, governance factors (board size; professionals on board; and frequency of board meetings) identify the influence of governance factors on zakat disbursement efficiency measures. The findings showthat there is a negative influence between board size and cost efficiency and no influence with disbursement and time efficiency. However, the relationshipbetween board size and disbursement and time efficiency is rejected because of insignificant results. Professionals on boards has a positive influence on disbursement, cost and time efficiency. Lastly, the frequency of board meetings positively influences disbursement efficiency and time efficiency. Frequency of board meetings showed a negative influence with cost efficiency. This research is significant as it could contribute to future discussions on the potential ways to improve zakat governance and efficiency in Indonesia. The outcomes from the discussions will be useful as a guide for policymakers looking to improve the zakat institution’s governance system. Keywords:Efficiency, Governance, Indonesia, Zakat